Research on Optimization Strategy of Regional Haze Governance Based on Synergy Effect--A Case of Central Plains City Group - Peng, Zili; Zhang, Ganggang (IOP conference series. Materials Science and Engineering, 2020)
As an atmospheric pollution, haze governance involves economic restructuring, energy change, environmental science, laws and regulations and other aspects, is an important measure to improve people's livelihood and optimize the mode of economic development. Through the analysis of the causes of haze and based on the synergistic effect, taking the Central China urban agglomeration as an example, from the perspective of public management, this paper puts forward the optimization strategy of regional haze co-governance, by constructing government departments 、 different levels 、 inter-regional intergovernmental coordination mechanisms, mechanisms for communication between local government and enterprises, citizen and local government、 enterprise's supervision mechanism, scientific research institutions and government、 enterprise's decision-making staff and technical support mechanism, to form a multi-subject, multi-pronged, seamless haze governance structure, which will prevent and control the tragedy of public sharing, promote the governance of public goods such as the atmosphere, break the administrative limitations of the administrative region, crack the decline of the Central Plains, and the development collapse of central region. It is of great significance to avoid the ecological overload and atmospheric pollution of the Central Plains urban agglomeration and to build a beautiful Central Plains.